Nano lead oxide and epdm composite for development of polymer based radiation shielding material: Gamma irradiation and attenuation tests. (March 2018) - Özdemir, T.; Güngör, A.; Akbay, I.K.; Uzun, H.; Babucçuoglu, Y.
Abstract: It is important to have a shielding material that is not easily breaking in order to have a robust product that guarantee the radiation protection of the patients and radiation workers especially during the medical exposure. In this study, nano sized lead oxide (PbO) particles were used, for the first time, to obtain an elastomeric composite material in which lead oxide nanoparticles, after the surface modification with silane binding agent, was used as functional material for radiation shielding. In addition, the composite material including 1%, 5%, 10%, 15% and 20% weight percent nano sized lead oxide was irradiated with doses of 81, 100 and 120 kGy up to an irradiation period of 248 days in a gamma ray source with an initial dose rate of 21.1 Gy/h. Mechanical, thermal properties of the irradiated materials were investigated using DSC, DMA, TGA and tensile testing and modifications in thermal and mechanical properties of the nano lead oxide containing composite material via gamma irradiation were reported. Moreover, effect of bismuth-III oxide addition on radiation attenuation of the composite material was investigated. Nano lead oxide and bismuth-III oxide particles were mixed with different weight ratios. Attenuation tests have been conducted to determine lead equivalent values for the developed composite material. Lead equivalent thickness values from 0.07 to 0.65 (2–6 mm sample thickness) were obtained. Highlights: Lead is conventionally used for X/Gamma ray shielding. However, lead aprons have many disadvantages including ease of crack. Nano materials has high surface to volume ratio. An elastomer based flexible composite material have been developed including nano lead oxide particles.